The political economy of food system transformation: Pathways to progress in a polarized world - Resnick, Danielle; Swinnen, Johan (International Food Policy Research Institute, 2023)
The current structure of the global food system is increasingly recognized as unsustainable. In addition to the environmental impacts of agricultural production, unequal patterns of food access and availability are contributing to non-communicable diseases in middle- and high-income countries and inadequate caloric intake and dietary diversity among the world’s poorest. While the need to transform food systems is widely accepted, the policy pathways for achieving such a vision often are highly contested, and the enabling conditions for implementation are frequently absent. Moreover, transformation implicitly requires reforms that depart from the status quo, which will generate resistance from those groups that stand to lose the most.